Exploring the Impact of Using Google Classroom on Speaking Virtual Class by Papuan EFL Students - Rahmawansyah Sahib; Erfin Wijayanti; Anggit Prasetio Nugroho; Syamsir bin Ukka; Andi Miftahul Maulidil Mursyid (Universitas Lancang Kuning, 2022)
This study will delineate and complete prior research gaps in the context of Papuan EFL students developing speaking abilities using Google Classroom. The main objective of this study is to investigate the impact of utilizing Google Classroom to develop speaking skills digitally. This study employed a qualitative descriptive approach, with data gathered through offline interviews and online observations of Tadris English students who developed speaking subjects. Then, interpretive thematic analysis is used to analyze the data throughout the process which consists of data collection, reduction, interpretation, presentation, and drawing conclusions. The results showed that students experienced several impacts from the use of Google classroom in learning speaking skills. The impact of using Google classroom is to save time and money, train student discipline in managing study time, make students more independent and proactive in accessing learning resources, trigger vocabulary changes, make students more difficult to get corrective feedback, limit student interaction directly, make students feel insecure, confused, and anxious, affecting student learning outcomes, understanding of the material delivered is not maximum. As a consequence, instructors should think more on the numerous preparations and instructional tactics utilized in teaching virtual speaking abilities. Of course, further study on the usage of Google Classroom for language skills other than speaking is required to enhance the conclusions of existing research. So that the guide for utilizing the learning platform in English learning is more detailed.